Adsorption of heavy metals solution on commercial activated carbon adsorbent: batch studies - Mohd Nazri Bin Shamsudin (School of Environmental Engineering, University Malaysia Perlis, 2011)
The ability of commercial activated carbon to adsorb Pb+ from aqueous solution has been investigated through batch experiments . The adsorption of lead onto commercial activated carbon has been found to depend on adsorbent dose, initial concentration and contact time. The experiments were carried out at natural dose, initial concentration and contact time. The experiments were carried out at natural solution ph. Equilibrium data fitted well with the Langmuir model and Freundlich model with a maximum adsorption capacity of 23.81 mg of Pb/g of commercial activated carbon.